2008
DOI: 10.1213/ane.0b013e318165e012
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intravenous Granisetron on the Sensory and Motor Blockade Produced by Intrathecal Bupivacaine

Abstract: We concluded that i.v. granisetron facilitated a faster recovery of sensory block after bupivacaine subarachnoid anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…Rashad et al [18] compared the hemodynamic effects of granisetron and ondansetron among patients undergoing cesarean deliveries under spinal anesthesia. However, this study demonstrated that granisetron had no effects on patients’ hemodynamic variables, in agreement with the findings of Mowafi et al [25].…”
Section: Discussionsupporting
confidence: 93%
“…Rashad et al [18] compared the hemodynamic effects of granisetron and ondansetron among patients undergoing cesarean deliveries under spinal anesthesia. However, this study demonstrated that granisetron had no effects on patients’ hemodynamic variables, in agreement with the findings of Mowafi et al [25].…”
Section: Discussionsupporting
confidence: 93%
“…7,8 There was reversal of antinociceptive effects of intrathecally administered serotonin in rat by selective 5-HT3 receptor anatagonist. 6 Ondansetron blocked nifedipine induced analgesia in rats. 9 After intrathecal injection of 0.5% bupivacaine both cerebrospinal fluid (CSF) and plasma, serotonin were determined radio enzymatically before and after anesthesia no change in plasma serotonin level but 300% increase in CSF serotonin level.…”
Section: Discussionmentioning
confidence: 98%
“…Granisetron, in contrast to ondansetron, which acts on mixed receptors, strongly and selectively binds to the 5-HT3 receptors with minimal or no affinity for other 5-HT receptors, or dopaminergic, adrenergic, histaminic, and opioid receptors and hence has faster regression of sensory effect in comparison to ondansetron. 15 The mechanism for 5-HT3-receptor antagonists for prevention of shivering is still unclear but is thought to be related to inhibition of serotonin reuptake on the preoptic anterior hypothalamic region and also serotonin (5-HT) is a critical thermoregulatory neurotransmitter, it decreases core temperature attenuation that triggers shivering. 16 In present study intravenous ondansetron 4mg, given five minutes before spinal anaesthesia effectively attenuated the fall in systolic blood pressure, diastolic blood pressure, and mean arterial pressure after spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 99%